Understanding the Needs for the Development of Entrepreneurship Competencies in Universities: A Comparative Analysis between Students and Employees. - Venesaar U.; Antonelli G.; Dorożyński T.; Duarte, H.; Kallaste M.; Riviezzo A.; Räisänen M.; Santos, S. C. (ESU Conference, 2021)
To successfully transition from university to the labour market, students in higher education are expected to improve knowledge, skills and other competences as outcomes of human capital. However, higher education institutions educate students by focusing on disciplinary, academic and technical skills (e.g., engineering, IT, business) while often lacking other important employability skills, like work readiness skills (Heijke, Meng, & Ris, 2003) or soft skills (World Economic Forum, 2018; Cross, Rebele & Grant, 2016). Responsibility, accountability, resilience and the ability to deal with challenges, spirit of initiative, the desire to take calculated risks, while accepting the challenges coming with them, are seen by some influencing chief executives (CEOs) as essential to achieve great results and to relaunch the economy of the countries to get out of the post Covid pandemic crisis. Similarly, business owners, particularly those owning micro and small businesses, have also focused their education on business skills while lacking specific entrepreneurship training. The development of their entrepreneurial skills (e.g., strategic thinking skills, creative problem solving) are particularly important because they enhance the performance of their ventures (e.g., Hynes & Richardson, 2007; Rowley & Mitchelmore, 2013). This constitutes the skills gap, which has important implications for curriculum design aiming to bridge the gap between the learning (university) and application (workplace) settings (Jackson 2013; Nabi 2003). Here, entrepreneurship competence is essential, as this is relevant across disciplines and in all modern careers and professional paths. Entrepreneurship competence constitute a comprehensive set of knowledge, skills and attitudes necessary for value creation during the implementation of ideas, developing an entrepreneurial mindset, and sustainable coping with work and everyday life (Venesaar et al, 2018).